Fiber optic polarization beam splitter using a reduced graphene oxide-based interlayer - Koo, Joonhoi; Park, Jaehyuri; Song, Yong-Won; Lee, Sangbae; Lee, Kwanil; Lee, Ju Han (ELSEVIER SCIENCE BV, 2015)
A fiber-optic polarization beam splitter (PBS) incorporating reduced graphene oxide (rGO) as a metallic interlayer material is proposed and demonstrated. It is experimentally shown that the polarization beam splitting function can readily be obtained using a coupler structure with a thin rGO layer embedded between two side-polished fibers due to induced transverse magnetic (TM) surface waves. The rGO layer was prepared by a simple method of dielectric GO spraying and ultraviolet irradiation-based reduction. The polarization extinction ratio of our implemented PBS was measured to be 14.5 dB at a wavelength of 1550 nm for both through- and cross-port. Its operating bandwidth was shown to be at least 100 nm (from 1500 to 1600 nm), which was limited by the maximum tuning range of the input tunable laser used. (C) 2015 Elsevier B.V. All rights reserved.